LYVE-1 immunohistochemical assessment of lymphangiogenesis in endometrial and lung cancer. Issue 2 (27th January 2005) - Koukourakis, M I; Giatromanolaki, A; Sivridis, E; Simopoulos, C; Gatter, K C; Harris, A L; Jackson, D G
Abstract : Aims/Methods: Normal and malignant pulmonary and endometrial tissues were analysed for lymphatic vessels to assess the process of lymphangiogenesis and its role at these sites, using specific immunostaining for LYVE-1 and the panendothelial marker CD31. Results: Lymphatics were clearly demonstrated in some normal tissues (myometrium, bronchial submucosa, and intestinal submucosa), but not in others (endometrium and alveolar tissue). LYVE-1 positive lymphatic vessels were detected at the tumour periphery of endometrial and lung carcinomas, but not within the main tumour mass. Double staining for LYVE-1 and the MIB1 proliferation marker revealed a higher proliferation index in lymphatic endothelial cells at the invading front of endometrial carcinomas, compared with myometrial areas distal to the tumour. Lung and endometrial carcinomas did not have an intratumorous lymphatic network. Conclusions: Although lymphangiogenesis may occur at the invading tumour front, incorporated lymphatics do not survive. Therefore, the dissemination of cancer cells through the lymphatics may occur by invasion of peripheral cancer cells into the adjacent normal lymphatics, or through shunts eventually produced at the invading tumour front as a consequence of active angiogenesis and lymphangiogenesis.